2018
DOI: 10.21276/aimdr.2018.4.2.rt2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Role of Oral Glutamine Supplementation in Radiation Induced Oral Mucositis in Head and Neck Cancers

Abstract: Background: Radiotherapy with or without concurrent chemotherapy forms the mainstay of treatment of head and neck cancers. Oral mucositis is one of the most common complications of Chemo Radio-Therapy(CRT) which outweighs the systemic complaints both in terms of severity and difficulty in management. The aim of our study was to assess the role of oral glutamine supplementation in prevention of oral mucositis in patients receiving CRT to the head and neck. Methods: This was a Prospective Randomized study perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…A total of 322 studies were captured at the first literature retrieval stage. Finally only 6 studies (19)(20)(21)(22)(23)(24) involving 441 patients were eligible for qualitative analysis, and 5 studies involving 279 patients were included in meta-analysis (19,20,(22)(23)(24). The flow diagram of retrieval and selection of literature was delineated in Figure 1.…”
Section: Results Of Study Retrieval and Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 322 studies were captured at the first literature retrieval stage. Finally only 6 studies (19)(20)(21)(22)(23)(24) involving 441 patients were eligible for qualitative analysis, and 5 studies involving 279 patients were included in meta-analysis (19,20,(22)(23)(24). The flow diagram of retrieval and selection of literature was delineated in Figure 1.…”
Section: Results Of Study Retrieval and Selectionmentioning
confidence: 99%
“…The doses and frequency of oral glutamine were slightly different. Moreover, four studies (20,(22)(23)(24) used CTCAE to evaluate the grade of OM and only one study (19) used WHO method, the other one (21) did not reported the method of evaluating OM. All studies reported that the baseline information between the glutamine group and the control group was not statistically significant.…”
Section: The Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations